Cilostazol Combats Lipopolysaccharide-Induced Hippocampal Injury in Rats: Role of AKT/GSK3β/CREB Curbing Neuroinflammation - Doaa Abou El-ezz; Waleed Aldahmash; Tuba Esatbeyoglu; Sherif M. Afifi; Marawan Abd Elbaset (Hindawi Limited, 2024)
Neuroinflammation is important in the pathophysiology of several degenerative brain disorders. This study looked at the potential neuroprotective benefits of cilostazol, a phosphodiesterase inhibitor, against LPS-induced hippocampus damage in rodents and the principal molecular involvement of AKT/GSK3β/CREB signaling pathways. Behavioral tests revealed that cilostazol successfully corrected LPS-induced neurobehavioral impairments. Furthermore, cilostazol therapy lowered hippocampal levels of amyloid beta 1-42 (Aβ1-42) and p-tau protein, both of which are critical pathological indicators of neurodegenerative disorders. Furthermore, cilostazol administration suppressed LPS-induced rises in hippocampus caspase-3 and NF-κB levels while elevating rat B-cell/lymphoma 2 (BCL2) and brain-derived neurotrophic factor (BDNF) levels, which are implicated in neuronal survival and synaptic plasticity. Cilostazol treatment also restored the decreased phosphorylation of protein kinase B (p-AKT) and reduced the elevated levels of phosphorylated glycogen synthase kinase-3 beta (p-GSK3β) and cAMP response element-binding protein (CREB) in the hippocampus of LPS-treated rats. Histopathological examination revealed that cilostazol ameliorated LPS-induced brain damage with reduced neuronal loss and gliosis. Immunohistochemistry analysis showed a decrease in Iba-1 expression, indicating a reduction in microglial activation in the cilostazol-treated group compared to the LPS group. The findings advocate that cilostazol exerts neuroprotective effects against LPS-induced hippocampal injury by modulating the AKT/GSK3β/CREB pathway and curbing neuroinflammation. Cilostazol may hold promise as a therapeutic agent for neuroinflammatory conditions associated with neurodegenerative diseases.